تأثير حجم الشركة ونشاطها في سوق الأوراق المالية على الإفصاح المحاسبي دراسة تجريبية - الطويل ليلى; زحلوط عفراء (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يركز هذا البحث على دراسة أثر أحد العوامل البيئية على مستوى الإفصاح المحاسبي الإلزامي وفقاً لمعايير التقرير المالي الدولية في الشركات، وهو عامل سوق رأس المال الذي يقاس من خلال بعدين هما: حجم الشركة في السوق المالي، ونشاط الشركة في هذه السوق. حيث يهدف هذا البحث إلى دراسة مستوى التباين في الإفصاح المحاسبي في التقارير المالية للشركات المدرجة بين سوقي دمشق وأبو ظبي للأوراق المالية، بالإضافة إلى دراسة العلاقة بين حجم الشركة في سوق رأس المال وبين مستوى الإفصاح المحاسبي، وكذلك دراسة العلاقة بين نشاط الشركة في سوق رأس المال وبين مستوى الإفصاح المحاسبي للشركات في هذين السوقين. خلص البحث إلى نتيجة مفادها وجود تباين في مستوى الإفصاح المحاسبي في التقارير المالية للشركات المدرجة (باستثناء الشركات المالية) بين سوقي دمشق وأبو ظبي للأوراق المالية، ولكن هذا التباين في مستوى الإفصاح المحاسبي لا يتأثر بحجم الشركة في السوق المالي، ولكنه يزداد بزيادة نشاط الشركة في هذه السوق. This research focuses on studying the impact of one of the environmental factors on the mandatory accounting disclosure level of firms according to international financial reporting standards (IFRS). It is the stock exchange factor, which has two dimensions: the company’s size in the stock exchange, and the company’s activity in the stock exchange. This research aims to study the variation level in the accounting disclosure in the financial reports of listed companies between Damascus Stock Exchange and Abu Dhabi Stock Exchange. It also aims to study the relationship between the company’s size in the stock exchange and the level of accounting disclosure, and to study the relationship between the company’s activity in the stock exchange and the level of accounting disclosure for companies in those stock exchanges. The research found that there is a variation in the level of accounting disclosure in the financial reports of listed companies, except for financial companies, between Damascus Stock Exchange and Abu Dhabi Stock Exchange, but this variation in the level of accounting disclosure is not affected by the company’s size in the stock exchange,. It is directly proportional to the company’s activity in this stock exchange.